PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI KERJA KARYAWAN PT. SATYA MANDALA PRATAMA WAY GIHAM - M. Agus Kurniawan; Nur Anisa Anggraini Sapitri; Palupi Indah Sari (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
This research aims to determine the influence of rewards and punishment onemployee work motivation at PT. Satya Mandala Pratama Way Giham. The datacollection technique used in this research was through distributingquestionnaires. The total population is 49 employees of PT. Satya MandalaPratama Way Giham. The data analysis technique used is multiple linearregression. Based on the results of partial hypothesis testing on the rewardvariable, the t-calculated value (6.827) > t-table (2.01290) means that there is aninfluence of rewards on the work motivation of PT employees. Satya MandalaPratama Way Giham. Meanwhile, the punishment variable has a t-count value(9.867) > t-table (2.01290), meaning that there is an influence of punishment onthe work motivation of PT employees. Satya Mandala Pratama Way Giham.Simultaneously, the Fcount was 379,918. These results are then compared withthe F table, the F table is obtained by looking at (df1= number of variables–1) =3-1=2 and (df2=n-k-1) = 49-2-1=46 at a 95% confidence level or α = 5%obtained Ftable 3.20. So Fcount 379.918>Ftable3.20 means that there is a significant influence of reward and punishment on thework motivation of PT employees. Satya Mandala Pratama Way Giham. Thecoefficient of determination (R2) obtained was 0.943. This shows that thecontribution of reward and punishment to work motivation is 94.3%, while theremaining 5.7% is influenced by other variables not mentioned in this research,such as internal factors, namely the desire to gain recognition and externalfactors, namely work environment conditions (Sutrisno, 2018:116)